Core muscle response times and postural reactions in soccer players and nonplayers - Borghuis, A. J.; Lemmink, K. A. P. M.; Hof, A. L. (Medicine & Science in Sports & Exercise, 2011)
ABSTRACT: Decreased core stability has been suggested to be associated with a higher occurrence of lower extremity injuries and low back pain. In a physical contact sport like soccer, direction-specific muscle reflex responses are crucial in maintaining core stability. Delayed core muscle response times repeatedly have been reported in patients with low back pain, but no study has compared core muscle reflex latencies and postural control between soccer players and less active nonplayers.